(untitled) (Swiss Medical Weekly, 2019)
This review is a simple guide to the deeper meaning of the association of a disease with a particular HLA allele. We will first review some principles of the function of the adaptive immune system, and some basic notions of autoimmune disease. In this, we will focus on the tripartite unity of the human leukocyte antigen (HLA) molecule, the peptide, and the T cell receptor that recognizes the complex of peptide and HLA molecule, placing emphasis on the function of the T cell receptor. We will also touch on the evolutionary forces shaping our adaptive immune system. Then we will apply this background to some current HLA data concerning the heterogeneity of psoriatic arthritis and the extent to which it is relayed to psoriasis, to illustrate how these principles are used to advance our understanding of the disease.